Evidence Of Platelet Activation by Flowcytometry Following Hormone Replacement Therapy In Post Menopausal Women - Hassan, Rosline (Universiti Sains Malaysia, 2009)
Platelet activation is one of the underlying mechanisms causing thrombosis. However women are generally protected from thrombotic events before menopause. Previous study showed that there was an evidence of platelet activation in post menopausal women and it was related to the level of serum estradiol yet remain questionable. Many immunoassays by EI.ISA were used to measure platelet activation. Thus out aim was to study the platelet activation by flow cytometry on post menopausal women receiving hormone replacement therapy. Methodology: Total of 48 volunteers postmenopausal women were recruited from gynaecology clinic. All women were later given HRT (Primarine or Progestigen) for 2 weeks. 10 mls of blood pre and post HRT was collected in 3.2% sodium citrate bottle. Platelet activation was measured by flow cytometric analysis using CD62P and PAC 1 FITC as monoclonal markers. Results: CD 62P and PAC1 FITC expression markers in post treatment with HRT show dramatically decreased compare to pre treatment level. CD62P were reduced significantly from 8.51 ± 12.56% to 3.15 ± 6.64% and PAC1 FITC from 41.75 ± 26.85% to 20.86 ± 19.02% after two weeks treatment (p<0.05). Conclusion: CD62P and PAC1 by flow cytometry are both useful markers to measure platelet activation. Short term treatment with Primarine or combined HRT reduced the circulating activated platelets as measured by flow cytometry which indicates a reduced risk of thrombotic event. Further study is required on its long term effect.